Evaluating the efficiency of agricultural land reclamation, and its impact on productivity Tobacco crop in Lattakia- Jableh - شيبان, نعمى; إبراهيم صقر; سوسن هيفا (Latakia University Journal -Biological Sciences Series, 2025)
The aim of this research is to study and analyze the production costs of local tobacco in Jableh, and to evaluate the efficiency of using reclaimed lands, by studying the economic efficiency of the tobacco crop in the study area, as it is one of the most important crops grown in reclaimed lands, relying in determining the cost of materials and wages on prevailing market prices in 2019.The research sample included 346 farmers in the twelve villages in Jableh. The results of the analysis of the efficiency of land reclamation showed an increase in returns and profitability for farmers, and an improvement in the economic situation of the productive areas, as the net farm income per dunum planted with tobacco before the reclamation operations amounted to 89950, and after reclamation operations amounted to379950 SYP. The profitability factor based on capital before reclamation operations reached 20.7%, after reclamation operations 72.7%, and based on production costs before reclamation operations 24.8%, and after reclamation operations123.1%. As for the capital recovery time indicator, it was 4.8 years before reclamation operations, 0.9 years after reclamation operations, and the overall economic efficiency index per dunum before reclamation was 1.2, and after reclamation was 1.71.